Mediasi Job Satisfaction Pada Pengaruh Leader- Member Exchange Dan Perceived Organizational Support Terhadap Organizational Citizenship Behavior PDAM Sleman - Sari, Susi Dian Martha; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – Quality public services are demands that must be met by organizations for the community. The perceived demand triggers the organization to provide excellent service in order to build an organization's image, especially in the public service process, which always gets the spotlight from the community. Public services are closely related to the role of human resources in an organization. Human resources that have good quality and support the success of the organization can be identified in employees with organizational citizenship behavior (OCB). The phenomenon that occurs at PDAM Sleman, namely poor customer service, is expected to be improved by increasing OCB. Aim – The research conducted aims to examine the effect of LMX and POS on OCB, with job satisfaction as a mediating variable. Design / methodology / approach – This study uses a quantitative approach and data collection in the form of filling out a questionnaire conducted to all employees of PDAM Tirta Sembada Sleman, as many as 65 employees by census. Findings – LMX, job satisfaction, and POS partially have a significant positive effect on organizational citizenship behavior. Leader-member exchange and perceived organizational support partially have a positive effect on OCB Perceived organizational support increases job satisfaction. Leader-member exchange has no significant effect on job satisfaction. The influence of leader-member exchange on OCB is mediated by job satisfaction. Conclusion – POS support plays a role in increasing job satisfaction and then has an impact on strengthening OCB. Research implication – Organizational leaders can improve the implementation of LMX, job satisfaction, and POS variables to increase employee OCB. Improvements made can support the organization's ability to provide good service as one of the public agencies in the region. Limitations – The research object only covers one branch of PDAM Sleman.